2006
DOI: 10.1111/j.1462-5822.2005.00622.x
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii inhibits ultraviolet light-induced apoptosis through multiple interactions with the mitochondrion-dependent programmed cell death pathway

Abstract: SummaryCells infected with the protozoan parasite Toxoplasma gondii are resistant to diverse apoptotic stimuli. In this study, we perform a detailed analysis of the manipulation of the mitochondrial arm of the apoptotic cascade by the parasite. Apoptosis was induced using irradiation with ultraviolet light (UV), and the kinetics of caspase activation, cytochrome c release and activation of the upstream signalling pathways were examined. The evidence clearly points to T. gondii targeting multiple steps in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
113
3
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(122 citation statements)
references
References 84 publications
3
113
3
3
Order By: Relevance
“…For example, Chlamydia trachomatis and Toxoplasma gondii are known to possess anti-apoptotic activity. 40,41 Recently, it has been shown that a substrate (SidF) of the Dot/Icm T4SS is involved in preventing apoptosis in infected cells with Legionella pneumophila. Apparently, SidF would abolish the activities of two proapoptotic proteins members of the Bcl-2 family: BNIP3 and Bcl-rambo.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Chlamydia trachomatis and Toxoplasma gondii are known to possess anti-apoptotic activity. 40,41 Recently, it has been shown that a substrate (SidF) of the Dot/Icm T4SS is involved in preventing apoptosis in infected cells with Legionella pneumophila. Apparently, SidF would abolish the activities of two proapoptotic proteins members of the Bcl-2 family: BNIP3 and Bcl-rambo.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a small subset of the host's mitochondria is associated with the PVM, an observation that is inconsistent with the global blockage of the mitochondrial pathway [97]. Also, products secreted by the parasite appear to be capable of limiting the activation of the executioner caspases 3 and 7, implying that rhoptry or dense proteins may be involved [98].…”
Section: Role Of the Death Receptor Pathwaymentioning
confidence: 99%
“…Activated caspase 9 cleaves caspase 3 leading to disassembly of the cell. T. gondii infected cells show only a small release of cytochrome c after induction of apoptosis via the mitochondrial pathway, thus dampening activation of caspases 9 in the apoptosome and subsequently precluding activation of caspase 3 ( Figure 2) [97,98]. However, it appears the parasite also independently targets caspases 3, since this enzyme remains in its inactive, zymogen form even in the presence of granzyme proteases that normally activate it upon delivery by cytotoxic T and natural killer cells [86].…”
Section: Role Of the Death Receptor Pathwaymentioning
confidence: 99%
See 2 more Smart Citations